Creatine supplementation (Sportscience, 1999)
Summary of the presentations at the 5th IOC Congress on Sport Sciences on creatine supplementation. Implication: Most researchers accept that creatine supplementation benefits performance of repeated bursts of all-out exercise. An important issue now is the effect of creatine on performance in specific sports. Two presenters addressed this question. There were also papers on the possible effects of creatine loading and on aspects of the loading regime.